UPAYA MENINGKATKAN PRESTASI BELAJAR PENJASORKES MATERI LEMPAR TURBO MELALUI METODE TEAM GAME TOURNAMENT PADA SISWA KELAS V SEMESTER 2 SDN WONOREJO 1 KARANGANYAR DEMAK - Suhartono, Suhartono (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2016)
The research problems are whether the use of the method TGT (Team Game Tournamen) orGaming Team can improve learning achievement of Physical Education and Health (PEH) on thesubject matter of the development of coordination numbers basic technique athletics (throwingturbo) at student Class V SD Negeri Wonorejo 1 Karanganyar Demak? The researches carriedout by two cycles of the first cycle and the second cycle with each cycle consisting of planning,implementation, observation and reflection. Of the implementation cycle I and II obtained anaverage yield of 69.94 value before repairs, completeness 18 out of 32 students (56.00%), the firstcycle value - average 74.24, completeness 25 out of 32 students (77.00% ), the second cyclevalue- average 80.00, completeness 30 from 32 students (95.00%). From these results it can beconcluded (i) an increase learning achievement PEH turbo throwing material through TGTmethod in class V students of SD Negeri Wonorejo 1 Academic Year 2015/2016.